Monitoring the habitat of protected plant species in verges near Kondoros (SE Hungary) - Sutyinszki, Zsuzsanna; Szentes, Szilárd (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
The vegetation of verges near Kondoros (South Tiszántúl, SE Hungary) was studied. Our aims were to survey the vegetation of verges, compare their species composition and explore the damaging factors. The field work was carried out in May 2010. One 55 m long transect of 11 units of 5 m x 2 m contiguous quadrats was recorded in each sample area. One main goal of our study was to create a method for monitoring vegetation changes in verges, so permanent transects were used. Beside the protected species we focused on invasive and shrub species. The species number was the lowest in a verge adjacent to a ploughed field. This is the habitat of one of the biggest population of Amygdalus nana near Kondoros and threatened by other shrub species. We found the highest species number on the habitat of Salvia nutans, which is mowed in each year and is protected by a bufferzone. The spread of shrub species is a big problem on some verges. The most frequent species are: Prunus spinosa, Robinia pseudoacacia and Sambucus nigra.
Keywords: loess vegetation; verges; shrub species; transect